Pengaruh Self Efficacy, Komitmen Organisasi Dan Motivasiterhadap Kinerja Pegawai Dinas Kesehatan Provinsi Bengkulu - Sri Wahyuni; Fahrudin Js Pareke; Praningrum Praningrum (Universitas Bengkulu, 2023)
The aim of this research is to examine and analyze the influence of self-efficacy, organizational commitment and motivation on employee performance. This research was conducted using a quantitative approach. The sample in this study was civil servants at the Bengkulu Provincial Health Service, totaling 309 employees and taken using the sencus method. The data analysis method used is multiple linear regression analysis. This research uses a casual study because it examines the influence of self-efficacy, organizational commitment and motivation on the performance of Bengkulu Provincial Health Service employees. Based on the research results, it is known that: (1) Self-efficacy has a significant positive effect on employee performance at the Bengkulu Provincial Health Service. This result means that the higher the self-efficacy, the higher the performance; (2) Organizational commitment has a significant positive effect on employee performance at the Bengkulu Provincial Health Service. This result means that the higher the organizational commitment, the higher the performance; (3) Motivation has a significant positive effect on employee performance at the Bengkulu Provincial Health Service. This result means that the higher the motivation, the higher the performance; and (4) Self-efficacy, organizational commitment and motivation have a significant effect on the performance of Bengkulu Provincial Health Service employees. This result means that the higher the Self-Efficacy, organizational commitment and motivation, the higher the performance.